Analyzing the Results of a Gerontology Data Collection Instrument - How do Specialists and Non-specialists Interpret the Data? - Santos Dos Santos, Suzane; Della Maggiori Orlandi, Brunela; Pereira Mota, Marcelle; Rios da Hora Rodrigues, Kamila (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
The Gerontological Care Plan (PAGe, in Portuguese) is an instrument used by Gerontology professionals in the multidimensional assessment of the elderly. The instrument can be applied by professionals who are not specialists, but who work with the elderly public. This paper reports on the experience of different profiles of professionals analyzing the results generated by this instrument. Our objective is to investigate whether a non-specialist in the field of Gerontology can see the results of the PAGe and make a referral or a proposal for an intervention with the target users that is close to the analysis made by the specialist. The need to test this hypothesis arose in the context of an extension project with the elderly, where it is not always possible to have a gerontologist present to apply this instrument, but it is part of the study protocol. Four volunteers analyzed the results of seven PAGes previous applied, two specialists in Gerontology and two non-specialists; the PAGe results used in the study consist of a table with scores that classify a risk called "biopsychosocial vulnerability of the elderly" and two radar-type graphs with information on the domains addressed in the instrument. The results show that both professionals and non-professionals interpret the graphs and tables in a similar way and have the same perceptions about the clinical condition of the elderly person, however, the specialist makes suggestions for more holistic referrals and interventions, considering different aspects of the life of this elderly person.